Actualization of Islamic Social Finance During Disasters: The Covid-19 Pandemic'`S Lessons In Indonesia - Djalaluddin, Ahmad; Kolilah, Kholilah; Danila, Nevi; Andriani, Sri (LPPM, Universitas Islam Syarifuddin Lumajang, 2023)
The COVID-19 pandemic is the best opportunity for applying Islamic social finance. The government’s limitations in tackling the impact of COVID-19 raise the participation of the Muslim community significantly. Applying Islamic social finance during COVID-19 taught us its effectiveness in dealing with disasters, especially in disaster-prone countries like Indonesia. This research combines normative and empirical aspects. The normative study is sourced primarily from the Qur'an, hadith, and scholarly ijtihad. The empirical study searches for empirical practices regarding Islamic social finance development in Indonesia. The study show that Islamic social finance practice in Indonesia during the COVID-19 has reflected a unique and rich actualization in terms of its basis, characteristics, varieties, and purposes; such as social investment, revolving assistance, exemption of tuition fees, and shadaqah of production tools. The community partnership patterns show that it has great potential to support the state's role in dealing with the disasters’ impact.